2015
DOI: 10.4103/0253-7613.169589
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine-induced acute generalized exanthematous pustulosis with positive patch-testing

Abstract: Acute generalized exanthematous pustulosis (AGEP) is a severe cutaneous adverse reaction, mostly induced by drugs. Hydroxychloroquine have been rarely reported in literature as a causative drug of this reaction. We report a case of AGEP induced by hydroxychloroquine with systemic involvement and confirmed by positive patch testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…The genetic and immunologic susceptibility to HCQinduced pustular cutaneous reaction may play an important role in this process or HCQ may induce a unique type of cutaneous reaction presented as AGEP-PP overlap. So regarding drug-induced nature, it is really in favor of AGEP, and regarding interval, it is really in favor of PP and about its course and management, it may be consistent with AGEP or PP (45% and 55%, respectively) [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic and immunologic susceptibility to HCQinduced pustular cutaneous reaction may play an important role in this process or HCQ may induce a unique type of cutaneous reaction presented as AGEP-PP overlap. So regarding drug-induced nature, it is really in favor of AGEP, and regarding interval, it is really in favor of PP and about its course and management, it may be consistent with AGEP or PP (45% and 55%, respectively) [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…There are many reports of unusual AGEPs after usage of HCQ, mainly in the setting of rheumatologic problems, which are somehow similar to PP clinical course and characteristics [16][17][18][19]. These types of HCQ-induced AGEPs usually have longer intervals from drug initiation, as well as a more severe, prolonged, and recalcitrant course [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Also, there are many reports of Stevens-Johnson/toxic epidermal necrolysis or drug reaction with eosinophilia and systemic symptoms-like AGEPs, especially as HCQ-induced AGEP [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Barbaud et al [8] in a multicenter study showed that 58% of patients with AGEP had positive patch tests; moreover, it was interesting that in one of those cases, a pustular eruption was re-induced after application of the patch test. Charfi et al [9] reported a case of AGEP induced by HCQ with positive patch test. In literature, few cases of relapse of AGEP after patch testing are described, even with a neg- ative patch test on the test side but cutaneous eruption in ectopic areas [10].…”
Section: Discussionmentioning
confidence: 99%
“…AGEP in association with administration of Hydroxychloroquine has been infrequently reported in the literature, with a total of twenty-one cases following a PubMed search using the terms 'Hydroxychloroquine' and 'Pustolosis.' Typically, this disease process is self-limited and requires basic supportive measures [7][8][9]. Rarely, AGEP can present in an atypical fashion with the development of blisters and vesicles that can coalesce, desquamate and form superficial erosions in an AGEP/SJS Overlap Syndrome [3,10,11].…”
Section: Discussionmentioning
confidence: 99%